The impact of different modalities on student retention and overall engagement patterns in open online courses. Issue 1 (2nd January 2018) - Friðriksdóttir, Kolbrún
ABSTRACT: This article presents an analysis of tracking data collected over eight years on 43, 000 users on Icelandic Online ( IOL ), seven open, guided online courses in Icelandic as a second language. The main objective in this study is to (a) map out retention for all the IOL courses, (b) compare retention on the same course delivered in three different modes; blended learning mode, distance learning mode, and self-directed mode, and (c) to investigate overall engagement patterns on IOL . The findings reveal low completion rates that vary by mode of delivery, identifying blended learning mode as most effective in retaining students. The results also reveal regular attrition patterns across all modes of delivery, with sharp drop-outs initially and concentrations of drop-outs at certain junctures in the courses. The drop-out patterns revealed in this study called for a re-evaluation of earlier parameters by which retention is measured, and especially what it means to 'complete a course'. Instead of considering course completion in light of 100% coverage, the findings show considerably higher retention on IOL when the parameters for course completion are adjusted to for instance 90% coverage of course content.